New Nile blue derivatives as NIR fluorescent probes and antifungal agents - Sousa, Rui P. C. L. (2019)
The synthesis of four new Nile Blue derivatives with hydrogen, propyl and/or aminopropyl groups as substituents of the amines of 5- and 9-positions is described. Photophysical properties were evaluated in acidified ethanol and aqueous solution at physiological pH. Antifungal activity is also studied through the obtention of MIC values.